Innovation Approach to Caries Treatment Among the Children Based on Algorithmic Diagnostics - Abduazimova, Lola Abrorxodjaevna; Abbasova, Diyora Bakhtiyorovna; Kuchkarova, Mukhayyo Kuranbaevna; Dinikulov, Djurabek Abdunabievich . (International Journal of Psychosocial Rehabilitation, 2020)
It is very important and purposeful to use cone bean CT in planning teeth treatment with a root perforation in order to reveal anatomic-physiological factures of the tooth and factors conducting, It is development and to evaluate foci of inflammation in periapical tissues.